Kahoot! Sebagai Inovasi Evaluasi Hasil Belajar Siswa Yang Efektif Dan Menyenangkan - Jarot Tri Bowo Santoso; Anik Widiyanti (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Student learning outcomes became an important part of decisions making about planning and implementing future learning. In general, the evaluation tools put the students under stress and lead to failure to achieve minimum graduation competencies. Kahoot! is one of the applications that can be used as an innovation in evaluation of student learning outcomes. The purpose of this study is to analyze the effectiveness and level of student acceptance of Kahoot! as a platform for evaluating Economics subject learning outcomes at SMA Negeri 1 Gemuh class X IPS. Respondents involved in the study were students of class X IPS 1 as the experimental class and class X IPS 2 as the control class, each class totaling of 30 students, at SMA N 1 Gemuh, Kendal Regency, Central Java. Data were taken through tests and in-depth interviews. The test result data were analyzed descriptively quantitatively. Analysis of interview data using an interactive model, namely data reduction, data display, and drawing conclusions. The results showed that the Kahoot! effective as a platform for evaluating economic learning outcomes. Kahoot app! is an innovation in evaluating learning outcomes that are more enjoyable.